Enzymatic hydrolysis of lignin by ligninolytic enzymes and analysis of the hydrolyzed lignin products. (May 2020) - Zhang, Sitong; Xiao, Jianlong; Wang, Gang; Chen, Guang
Highlights: Alkali lignin degradation by three enzymes was examined. Structural and compositional changes to degraded alkali lignin were characterized. Degradation products were identified by GC–MS, and production pathways analyzed. Synergy among ligninolytic enzymes gave the highest degradation levels of lignin. Enzymes enabled ring-opening of benzene structures and rupture of chemical bonds. Abstract: The degradation of alkali lignin was studied using three types of pure enzyme, Lac, LiP, and MnP, using alkali lignin as substrate. The alkali lignin removal rate was found to be 28.98% when Lac, LiP, and MnP were cultured together for alkali lignin degradation. Changes in the structure and composition before and after degradation were characterized by scanning electron microscopy, Fourier-transform infrared spectroscopy, nitrogen adsorption, and gas chromatography–mass spectrometry. The degradation product pathways were analyzed. The enzyme was proven to degrade alkali lignin, resulting in destruction of the alkali lignin structure, ring-opening of the macromolecular benzene ring structure and groups in alkali lignin, and chemical bond cleavage. This study explains the principle of alkali lignin enzymatic hydrolysis and provides a theoretical basis for the biodegradation of lignin.